(untitled) (The Review of Diabetic Studies, 2025)
Background: Palliative care enhances the quality of life for patients with chronic and life-limiting illnesses by addressing physical, emotional, and psychosocial needs. Nursing-led palliative interventions have emerged as effective, patient-centered approaches emphasizing holistic care, communication, and continuity. Aim: This systematic review aimed to evaluate the effectiveness of nursing-led palliative care interventions in improving the quality of life among adult patients with chronic or terminal illnesses between 2021 and 2025. Method: A systematic search was conducted across PubMed, Scopus, CINAHL, Web of Science, and Google Scholar following PRISMA guidelines. Studies were included if they examined nursing-led palliative interventions and reported patient quality-of-life outcomes. Ten high-quality studies—comprising randomized controlled trials, cohort, mixed-method, and meta-analytic designs—were analyzed using thematic and narrative synthesis. The Joanna Briggs Institute (JBI) checklist was used for quality appraisal. Results: Nursing-led interventions consistently improved emotional well-being, communication, and satisfaction. Long-term programs achieved better symptom control, while meta-analyses indicated comparable or superior results to physician-led models. Telehealth programs showed moderate yet positive outcomes when supported by structured follow-up and education. Conclusion: Nursing-led palliative interventions significantly enhance patient quality of life through empathy, holistic care, and sustained support. Strengthening nurse leadership, education, and institutional frameworks is vital to fully integrate these models into healthcare systems.